2011
DOI: 10.1186/bcr2933
|View full text |Cite
|
Sign up to set email alerts
|

The non-protein coding breast cancer susceptibility locus Mcs5a acts in a non-mammary cell-autonomous fashion through the immune system and modulates T-cell homeostasis and functions

Abstract: IntroductionMechanisms underlying low-penetrance, common, non-protein coding variants in breast cancer risk loci are largely undefined. We showed previously that the non-protein coding mammary carcinoma susceptibility locus Mcs5a/MCS5A modulates breast cancer risk in rats and women. The Mcs5a allele from the Wistar-Kyoto (WKy) rat strain consists of two genetically interacting elements that have to be present on the same chromosome to confer mammary carcinoma resistance. We also found that the two interacting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…DMBA or MNU treatment of the susceptible WF.WKy rats routinely yields ∼8 or ∼4 mammary carcinomas per rat at 15 weeks post-treatment, respectively [35]. The treated and age-matched untreated control rats were sacrificed 1, 2, 4 or 15 weeks after carcinogen exposure and their mammary glands or frank mammary carcinomas were isolated.…”
Section: Methodsmentioning
confidence: 99%
“…DMBA or MNU treatment of the susceptible WF.WKy rats routinely yields ∼8 or ∼4 mammary carcinomas per rat at 15 weeks post-treatment, respectively [35]. The treated and age-matched untreated control rats were sacrificed 1, 2, 4 or 15 weeks after carcinogen exposure and their mammary glands or frank mammary carcinomas were isolated.…”
Section: Methodsmentioning
confidence: 99%
“…Such loci may operate directly within mammary epithelial cells or may be mediated by the activities of non-mammary cells. We have recently reported that the rat Mcs5a locus acts via the immune system and that the resistant allele of Mcs5a is associated with increased frequency and functional activity of γδ T cells within spleen and mammary epithelium (2). These findings suggest that engaging key immune cell types to phenocopy the effects of the resistant Mcs5a allele may represent an effective breast cancer prevention strategy.…”
Section: Introductionmentioning
confidence: 99%
“…On the assumption that tumor suppressors are conserved across mammalian species, investigators have carried out numerous genetic linkage studies in rats to identify genes responsible for this differential susceptibility [3], [4], [5], [6], [7], [8], [9], [10]. Prior studies in rats identified 29 strain-specific mammary carcinoma susceptibility (Mcs) loci [11], [12].…”
Section: Introductionmentioning
confidence: 99%